RECALIBRATING DAILY LIFE: SYNCHRONIZING, COORDINATING, AND SCHEDULING THROUGH SMARTPHONES - Hand, Martin (AoIR Selected Papers of Internet Research, 2018)
"This paper examines individual framings and experiences of temporal management via smartphone applications. It asks: to what extent and in what ways do configurations of smartphones and scheduling applications intervene in and restructure the temporality of practices and people’s experiences of time? The paper draws upon in-depth semi-structured interview material with (a) professional urban and suburban householders (N=25), (b) individuals transitioning to retirement (N=20), and (c) university students (N=25) to examine how a range of temporal expectations are being perceived, articulated, and negotiated in practice. Interviews included talking through temporal data of many kinds on personal devices. The analytic questions guiding interviews were: where do identifiable expectations about temporal synchronization, coordination, duration, reciprocity, and productivity come from? What are the relations between institutionally defined temporal expectations and subjective experiences of temporal ordering? Does data produced through daily activities alter the temporal contours of those activities? Are social actors reorienting themselves in-time, in relation to mediatized temporal expectations? In terms of findings, four modes of temporal management are identified and described in relation to demographic information. Following Sharma (2014), these are expressed here as ‘recalibrations’ – managing precariousness; synchronizing (to) the time of others; temporal self-disciplining; filling in future time - stressing the different ways in which temporal demands are perceived and experienced, leading to alternative efforts to coordinate and synchronize different elements of daily life through interconnected smartphone anchored applications."